Thermal Enhancement of Ribbed Double Pipe Heat Exchangers Using Titanate Nanofluids for Advanced Heat Transfer Systems - Mohammed A. Al-Behadili; Abdulwahid A. Al-Hajjaj (Bumi Publikasi Nusantara, 2025)
This study investigates the improvement of thermal performance in smooth and ribbed double-pipe heat exchangers using titanium-based nanofluids. Titanate nanoparticles and nanotubes were synthesized and dispersed in water through a two-step method to ensure stable nanofluid mixtures. Experimental trials were conducted at varying concentrations and flow rates to evaluate temperature difference, heat transfer rate, coefficient, and efficiency. Results indicate a consistent performance increase in ribbed configurations, with titanium nanotubes outperforming their nanoparticle counterparts. This enhancement occurs because the ribbed geometry promotes turbulence while the nanotube’s morphology increases thermal conductivity and energy interaction with the fluid. The combination of structural design and nanofluid science enhances energy efficiency in heat exchanger systems. These findings support the development of more effective thermal systems through the integration of nanotechnology and mechanical design, aligning with advancements in science and engineering education.